Nutrient L-Alanine-Induced Germination of Bacillus Improves Proliferation of Spores and Exerts Probiotic Effects in vitro and in vivo - Lu, Shuang; Liao, Xianyin; Zhang, Li; Fang, Ying; Xiang, Meixian; Guo, Xiaohua (Frontiers in Microbiology, 2021)
As alternatives to antibiotics in feed, probiotic Bacillus carries multiple advantages in animal production. Spores undergo strain-related germination in the gastrointestinal tract, but it is still unknown whether the probiotic function of the Bacillus depends on the germination of spores in vivo. In this study, based on 14 potential probiotic Bacillus strains from fermented food and feed, we detected the germination response of these Bacillus spores in relation to different germinating agents. The results showed the germination response was strain-specific and germinant-related, and nutrient germinant L-alanine significantly promoted the growth of strains with germination potential. Two strains of Bacillus subtilis, S-2 and 312, with or without a high spore germination response to L-alanine, were selected to study their morphological and genic differences induced by L-alanine through transmission electron microscopy and comparative transcriptomics analysis. Consequently, after L-alanine treatment, the gray phase was largely increased under microscopy and the expression of the germination response genes was significantly up-regulated in the Bacillus subtilis S-2 spores in comparison to the Bacillus subtilis 312 spores (P < 0.05). The protective effect of L-alanine-induced spore germination of the two strains was comparatively investigated both in the IPEC-J2 cell model and a Sprague-Dawley (SD) rat model challenged by enterotoxigenic Escherichia coli K99. The result indicated that L-alanine helped Bacillus subtilis S-2 spores, but not 312 spores, to decrease inflammatory factors (IL-6, IL-8, IL-1β, TNF-α) (P < 0.05), and promote the expression of occludin in IPEC-J2 cells. Besides, supplement with L-alanine-treated Bacillus subtilis S-2 spores significantly improved the growth of the SD rats, alleviated histopathological GIT lesions, and improved the ratio of jejunal villus length to crypt depth in comparison to the Bacillus subtilis S-2 spores alone (P < 0.05). Improved species diversity and abundance of fecal microbiota were only observed in the group with L-alanine-treated S-2 spores (P < 0.05). The study demonstrates L-alanine works well as a probiotic Bacillus adjuvant in improving intestinal health and it also provides a solution for the practical and accurate regulation of their use as antibiotic alternatives in animal production.